2018
DOI: 10.1530/eje-18-0549
|View full text |Cite
|
Sign up to set email alerts
|

Is receptor profiling useful for predicting pituitary therapy?

Abstract: Medical treatment of pituitary tumours may present important challenges in the presence of resistance to first line therapy. In this setting, the availability of specific markers of responsiveness/resistance could be helpful to provide tailored patients' treatment. Pituitary receptor profiling has emerged as a potentially useful tool for predicting the response to specific pituitary-directed medical therapy, mainly somatostatin analogues and dopamine agonists. However, its utility is not always straightforward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 86 publications
0
16
0
Order By: Relevance
“…A number of factors might predict a poor response to lanreotide Autogel in the present patient which could have been considered before treatment, thus obviating the need and additional cost of a non-efficacious treatment. Young age at presentation, male gender, high baseline hormonal levels, high signal intensity on T2-weighted MRI, and the histopathology of a sparsely-granulated pattern [13,27] with intense expression of SSTR5 and low expression of E-cadherin [13,14,18,28], are all markers pointing to an expected poor response to a predominant SSTR2 agonist such as lanreotide. Pasireotide is a second-generation SSA with higher affinity for SSTR5 (besides SSTR1,-2,-3) [24,28].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A number of factors might predict a poor response to lanreotide Autogel in the present patient which could have been considered before treatment, thus obviating the need and additional cost of a non-efficacious treatment. Young age at presentation, male gender, high baseline hormonal levels, high signal intensity on T2-weighted MRI, and the histopathology of a sparsely-granulated pattern [13,27] with intense expression of SSTR5 and low expression of E-cadherin [13,14,18,28], are all markers pointing to an expected poor response to a predominant SSTR2 agonist such as lanreotide. Pasireotide is a second-generation SSA with higher affinity for SSTR5 (besides SSTR1,-2,-3) [24,28].…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemistry of somatotroph tumors has been problematic, with heterogeneity in tumoral SSTR expression in different studies, variability of techniques to detect SSTR status, and the pre-operative treatment of tumors, all contributing to highly variable results [13,14]. In cases where both SSTR2/5 are intensively positive on IHC, an additional factor such as E-cadherin may guide further treatment [13,27]. It has been suggested that additional biomarkers could be used to predict the biological behavior of the tumor and its response to treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Molecular profiling has become an emerging method to characterise a large variety of molecular markers. qPCR is widely used in research settings, but has not yet been established in a daily clinical diagnostic routine setting and validation in well characterised cohorts undergoing standardised SRLs treatment, with well-defined outcome parameters is warranted (38,80).…”
Section: First-generation Srlsmentioning
confidence: 99%